Small Molecule Treatments Improve Differentiation Potential of Human Amniotic Fluid Stem Cells - Zentelytė, Aistė; Žukauskaitė, Deimantė; Jacerytė, Ieva; Borutinskaitė, Veronika V.; Navakauskienė, Rūta (Frontiers in Bioengineering and Biotechnology, 2021)
Human amniotic fluid stem cells (AFSC) are an exciting and very promising source of stem cells for therapeutic applications. In this study we investigated the effects of short term treatments of small molecules to improve stem cell properties and differentiation capability. For this purpose we used epigenetically active compounds such as DNA methyltransferase (DNMT) inhibitor Decitabine, histone deacetylase inhibitors Trichostatin A (TSA) and sodium butyrate (NaBut), as well as multifunctional molecules of natural origin such as retinoic acid (RA) and vitamin C (vitC). We observed that combinations of these compounds triggered upregulation of genes involved in pluripotency (KLF4, OCT4, NOTCH1, SOX2, NANOG, LIN28a, CMYC) which was determined by reverse‐transcription quantitative polymerase chain reaction (RT-qPCR). Also, some alterations in cell surface marker expression was established by flow cytometry with the most explicit changes in the expression of CD105 and CD117. Analysis of cellular energetics performed using Seahorse analyzer and assessment of gene expression related to cell metabolism and respiration (NRF1, HIF1α, PPARGC1A, ERRα, PKM1, PDK1, LDHA) revealed that small molecule treatments stimulate AFSCs towards a more energetically active phenotype. To induce cells to differentiate towards neurogenic lineage several different protocols including commercial supplements N2 and B27 together with RA were used and compared to the same differentiation protocols with the addition of a pre-induction step consisting of a combination of small molecules (vitC, TSA and RA). During differentiation the expression of several neural marker genes was analysed (Nestin, MAP2, TUBB3, ALDH1L1, GFAP) by RT-qPCR and the beneficial effect of small molecule treatment on differentiation potential was observed with upregulated gene expression. The results of this study provide valuable insights for the potential use of short term small molecule treatments to improve stem cell characteristics and boost differentiation potential of AFSCs.